Interbank network and bank bailouts: Insurance mechanism for non-insured creditors? - Tim Eisert; Christian Eufinger (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
This paper presents a new theory that explains why it is beneficial for banks to be highly interconnected and to engage in herding behavior. It shows that these two important causes of systemic risk are interdependent and thus cannot be considered in isolation. The reason is that banks have an incentive to exploit their implicit government guarantees by artificially channeling funds through the interbank market, which leads to high interconnectedness. Moreover, given that banks are highly interconnected, they are incentivized to invest in correlated portfolios to minimize contagion risks and thereby maximize the government subsidy per invested unit of capital.
Keywords: G01; G21; G28; 330; bailout; systemic risk; interconnectedness; herding; interbank network